Analysis of Legal Responsibility of The Press in The Perspective of John Rawls' Theory of Justice - Susanto, Joko; Rahma, Dhiny Ligi; Ilmanta Rian, Rinanda Asrian (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze how legal accountability of the press can be understood and interpreted within the framework of John Rawls' theory of justice. The methodology used in this study is theoretical analysis and qualitative approach. The qualitative approach is used to explore the concepts related to legal accountability of the press and John Rawls' theory of justice. In addition, theoretical analysis is carried out to understand the relevance between legal accountability of the press and the principles of justice introduced by John Rawls. This study concludes that in the perspective of John Rawls' theory of justice, legal accountability of the press must be based on the principle of fair equality. This means that every action or report published by the media must pay attention to justice and truth, and respect the rights of individuals in society. Thus, legal accountability of the press is not only limited to the legal aspect, but also to the moral and ethical aspects in conveying information to the public. The results of this study provide an important contribution to the understanding of legal accountability of the press from the perspective of John Rawls' theory of justice. The implication of this study is the importance of the media in carrying out its role as a guardian of justice and truth in society. Therefore, there needs to be a regulation that ensures that the media adheres to the principles of justice and accountability in carrying out its duties as a conveyor of information